Generasi Anti Korupsi, Membangun Indonesia Yang Lebih Baik - Imelda Sahfitri; Reynaldi Saputra; Fakhrul Ilham; Nur Afriyanti; Ilham Hudi (Politeknik Negeri Padang, 2025)
Corruption remains one of the most significant challenges to sustainable development in Indonesia, undermining economic growth, social justice, and political integrity. The younger generation plays a crucial role in shaping a culture of anti-corruption that can help address this issue. As digital natives, this generation is well-equipped with the tools and skills necessary to advocate for transparency, accountability, and integrity. This research aims to explore the vital contributions of the youth in combating corruption and establishing an anti-corruption culture in Indonesia. The study highlights the importance of education in embedding anti-corruption values, focusing on both formal and informal education systems. Integrating anti-corruption teachings into school curricula is essential for fostering a sense of responsibility and ethical awareness among young individuals. Ultimately, this paper argues that the younger generation is not only the future of Indonesia but also its most powerful ally in the fight against corruption. Their involvement in anti-corruption initiatives can transform Indonesia into a more just, transparent, and accouable society.